Out of the shadows - Hooper, Kay (Bantam Books, 2000)
"To catch this killer, she must break every rule and cross every line. A picture-perfect Tennessee town has just become a monster's hunting ground. Two bodies are found tortured to death. A third person goes missing. What little evidence is left behind defies all explanation. Is the terror just beginning? Or have the good citizens of Gladstone harbored a dark secret for a long time? Sheriff Miranda Knight is determined to make her small town safe once more. And she does what she swore she would never do: involve FBI profiler Noah Bishop. He's the one man who knows about her unique abilities, and that knowledge almost destroyed her and her sister years ago. Now, as Bishop arrives with his team of agents, Miranda must learn to trust him and use her abilities once more. For they're about to go on the hunt for a killer whose madness has no bounds, a killer who knows exactly how to destroy Miranda: by preying on her sister."--Amazon.